Transcriptomic insights into the molecular response of Saccharomyces cerevisiae to linoleic acid hydroperoxide. (December 2013) - O'Doherty, P. J.; Lyons, V.; Higgins, V. J.; Rogers, P. J.; Bailey, T. D.; Wu, M. J.
Abstract: Eukaryotic microorganisms are constantly challenged by reactive oxygen species derived endogenously or encountered in their environment. Such adversity is particularly applied to Saccharomyces cerevisiae under harsh industrial conditions. One of the major oxidants to challenge S. cerevisiae is linoleic acid hydroperoxide (LoaOOH). This study, which used genome-wide microarray analysis in conjunction with deletion mutant screening, uncovered the molecular pathways of S. cerevisiae that were altered by an arresting concentration of LoaOOH (75 μM). The oxidative stress response, iron homeostasis, detoxification through PDR transport and direct lipid β-oxidation were evident through the induction of the genes encoding for peroxiredoxins ( GPX2, TSA2 ), the NADPH:oxidoreductase ( OYE3 ), iron uptake ( FIT2, ARN2, FET3 ), PDR transporters ( PDR5, PDR15, SNQ2 ) and β-oxidation machinery ( FAA2, POX1 ). Further, we discovered that Gpx3p, the dual redox sensor and peroxidase, is required for protection against LoaOOH, indicated by the sensitivity of g px3Δ to a mild dose of LoaOOH (37.5 μM). Deletion of GPX3 conferred a greater sensitivity to LoaOOH than the loss of its signalling partner YAP1 . Deletion of either of the iron homeostasis regulators AFT1 or AFT2 also resulted in sensitivity to LoaOOH. These novel findings for Gpx3p, Aft1p and Aft2p point to their distinct roles in response to the lipid peroxide. Finally, the expression of 89 previously uncharacterised genes was significantly altered against LoaOOH, which will contribute to their eventual annotation.